2016
DOI: 10.1111/ijd.13443
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of 100 chronic thalassemic leg wounds by plasma‐rich platelets

Abstract: This study will help extrapolation of the use of PRP for at least thalassemic leg wound treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…After 100 chronic thalassemic leg wounds were treated successfully with PRP gel, its uses were expanded further. 98 When considering the potential benefits of PRP as an adjunctive therapy, the aggressive debridement used to treat wound infections should be considered. 99 Basic research and clinical studies have demonstrated that topical application of PRP is a useful auxiliary therapy for wound infections.…”
Section: Treatment For Hidradenitis Suppurativamentioning
confidence: 99%
“…After 100 chronic thalassemic leg wounds were treated successfully with PRP gel, its uses were expanded further. 98 When considering the potential benefits of PRP as an adjunctive therapy, the aggressive debridement used to treat wound infections should be considered. 99 Basic research and clinical studies have demonstrated that topical application of PRP is a useful auxiliary therapy for wound infections.…”
Section: Treatment For Hidradenitis Suppurativamentioning
confidence: 99%
“…Recently research has shown that 100 chronic thalassemic leg wound were treated by PRP gel and wound size reduction was observed after 4 weeks [4]. Our patient received both autologous PRP subcutaneously and gel topically followed by an optimized diet.…”
Section: Discussionmentioning
confidence: 92%
“…The standard treatment of diabetic ulcers includes measures to optimize glycemic control as well as extensive debridement, infection elimination by antibiotic therapy based on wound pathogen cultures, usage of moisture dressings, and offloading high pressure from the wound bed [2]. Cumulative studies have found that autologous platelet concentrate with growth factors or platelet-rich plasma (PRP) may accelerate wound healing [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 PRP has been recently used also with local microinjections in the cure of nonhealing ulcers. 63 Trapasso and colleagues 64 reported the excellent result of the treatment with platelet-derived GFs and noncultured autologous cell suspension collected by a single-use device in a chronic vasculitic ulcer.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%